IMPLEMENTASI PENDEKATAN PENDIDIKAN IMAN DENGAN MEDIA LUKIS BAGI KELOMPOK ANAK AUTIS - Dadi, Kanisius Komsiah (Lembaga Penelitian STKIP Widya Yuwana, 2025)
Autistic individuals often face discrimination and social isolation in the environment. To unlock their potential and encourage physical and emotional development, they need ongoing exceptional support using various supportive media (Inclusive faith education). This research answers the problem of how inclusive education for autistic children is developed through various suiTabel media, one of which is painting media. Painting can serve as a suiTabel medium for faith education for these children. This is important to adjust to the child's level of autism. The expression of faith is unique and often contains artistic value. The process of faith education can be adapted to accommodate individuals with different levels of thinking, feeling, and acting abilities. Through painting activities, autistic children can express their faith and trust in Christ, using their unique strengths and limitations. Researcher used a qualitative descriptive method, focusing on a group of autistic children and their parents/companions. The data collection technique included observation of 17 autistic children and interviews with 17 parents and two companions to support the research objectives. Observation focuses on the expression of children's thoughts and feelings in the form of paintings after receiving short-simple teaching. The interview focuses on introducing children's characters based on the views of parents and companions. The study's findings show that before autistic children are actively involved in the faith education process, parents and companions (catechists) are important to understand each child's interests and potential. Painting activities are not necessarily suiTabel for all types or levels of autism. Parents and catechists are important in designing faith education content for their children according to their needs and circumstances.